“Nós somos tão invisíveis aos poderes”: a lei Maria da Penha nas periferias de João Pessoa - Cavalcanti, Luanna Karolyne de Oliveira (2021)
Domestic violence against women is a problem that has been gaining visibility in the country. Whether because of the numbers, wich show the exponential growth of records and express their incidence, or due to different types of violence in the daily lives of women, this theme becomes the focus of more in-depth studies every day. Studies point to the racial character of domestic violence against women, considering the dynamics created in the intersection between gender, race and class. The Maria da Penha Law (No. 11.340/06), is a sophisticated strategy for dealing with it as well as protective limits. In this direction, the research aims to investigate the particularities of women living on the outskirts of the city of João Pessoa-PB in accessing the protective mechanisms of the Law. The methodology of life stories told by women was used. The data presented here were accessed through field work. The stigmas linked to the peripheral territory added to situations of institutional revictimization figure in the narratives as a complexifying factor in accessing protection mechanisms. The interlocutors of this research made it possible to understand the particular dynamics thath involves the context of violent marital relationaships, how gender performances are triggered and transgressed, also paying attention to the environment of social tolerance that still surrounds domestic violence against women.